Answer:
3x-20
Step-by-step explanation:
Answer:
5 ft
Step-by-step explanation:
The previous jumper jumped p
The new jumper jumped p*1.1 and that was 5.5 ft
1.1p = 5
Divide each side by 1.1
1.1p/1.1 = 5.5/1.1
p = 5
The previous jumper jumped 5 ft
Answer:
5 ft
Step-by-step explanation:
Let the height of the previous jump be represented by j. Then 1.1j = 5.5 ft.
Dividing both sides by 1.1, we get j = 5 ft. This was the height of the previous jump.
Answer:
20
Step-by-step explanation:
Answer:
20
Step-by-step explanation: